Molecular epidemiological and clinical aspects of enterovirus infection in the south of Russia - Kovalev, E. V.; Tverdokhlebova, T. I.; Simovanyan, E. N. (Medicinskij vestnik Ûga Rossii, 2023)
Objective : the study of molecular epidemiological and clinical aspects of EVI in the Rostov region for the period 2006-2020. to improve the disease surveillance system. Research methods: epidemiological, virological, molecular biological (PCR, sequencing, phylogenetic analysis), microbiological, statistical. Materials and methods : the analysis of medical records of 139 patients with EVI was carried out. Samples of biomaterial (feces, throat swab) from 17293 people, samples from environmental objects (2710 samples), strains of enteroviruses (EV) in the amount of 142 specimens were studied. Results : in the Rostov region until 2013. sporadic incidence of EVI prevailed with registration from 1 to 38 cases per year. June 2013 there was a sharp increase in the incidence of EVI with the formation of local foci in organized groups, associated with the circulation of a new genotype — EV 71 type of subgenotype C4 of “Chinese” origin (622 patients with EVI were registered, one death). The clinical features of the disease were determined: acute onset with manifestations of intoxication, foot and mouth disease-like syndromes, followed by the development of CNS pathology in 37.4% of patients. According to the results of sequencing of biomaterial samples from patients and virus carriers for the period 2006-2020. EVs of 22 types were detected. Conclusions : EVs are subject to intense genetic variability, due to which new genovariants pathogenic for humans may appear. The change in EV genotypes, which dominated the circulation among the population of the Rostov region, determined the rise in the incidence of EVI in 2013. A significant diversity of non-polio EV genotypes was revealed, while the structure of EV genovariants changed in different years.